Evaluation on training about cardio-pulmonary resuscitation knowledge and first-aid skills for community-dwellings (社区公众心肺复苏知识和技能培训效果分析) - WANG Le (王乐); LUO Shan (罗珊) (中西医结合护理, 2022)
Objective To investigate the current situation and potential influencing factors of cardio-pulmonary resuscitation (CPR)knowledge and first-aid skills among community-dwellings, and to evaluate the community-based CPR training program. Methods A random sample of 300 residents living in a certain community in Yingze District, Taiyuan were recruited for the field investigation. A community-based training group was established to provide CPR knowledge and first-aid skills training program for those recruited community-dwellings. The residents’ knowledge about CPR and related first-aid skills were assessed before and after training. Results A total of 300 valid questionnaires were received, and the recovery rate of survey was 93. 75%. The rates residents’ awareness about CPR theoretical knowledge such as diagnosis of sudden cardiac arrest were increased after training (P＜0. 01). The scores of CPR theory and first-aid skills evaluation after training were higher than those before training(P＜0. 01). Conclusion The community-based training is effective to improve the CPR awareness and first-aid skills among community-dwellings (目的 了解社区公众心肺复苏(CPR)认知现状及其影响因素, 探讨对社区公众进行CPR知识和急救技能培训的效果。方法 采用随机抽样方法对山西省太原市迎泽区共320名社区居民进行CPR相关知识的基线调查。成立院外CPR培训小组, 对社区居民进行CPR知识和急救技能培训。对比培训前和培训后社区居民对CPR理论知识和急救技能掌握情况。结果 共发放调查问卷320份, 回收300份, 回收有效率为93. 75%。培训后, 社区居民对心搏骤停判断、CPR体位等CPR理论知识知晓率较培训前提高, 差异有统计学意义(P＜0. 01)。培训后, 社区居民CPR理论知识与实践技能考核成绩较培训前提高, 差异有统计学意义(P＜0. 01)。结论 通过组建院外培训小组, 以社区为单位开展CPR知识和急救技能培训, 对社区公众掌握一定的急救技能及提高应急能力具有较好的效果。)